The Role of Morphology in Optically Switchable Transistors Based on a Photochromic Molecule/p‐Type Polymer Semiconductor Blend. (18th November 2019) - Carroli, Marco; Duong, Duc T.; Buchaca‐Domingo, Ester; Liscio, Andrea; Börjesson, Karl; Herder, Martin; Palermo, Vincenzo; Hecht, Stefan; Stingelin, Natalie; Salleo, Alberto; Orgiu, Emanuele; Samorì, Paolo
Abstract: The correlation between morphology and optoelectronic performance in organic thin‐film transistors based on blends of photochromic diarylethenes (DAE) and poly(3‐hexylthiophene) (P3HT) is investigated by varying molecular weight ( M w = 20–100 kDa) and regioregularity of the conjugated polymer as well as the temperature of thermal annealing (rt‐160 °C) in thin films. Semicrystalline architectures of P3HT/DAE blends comprise crystalline domains, ensuring efficient charge transport, and less aggregated regions, where DAEs are located as a result of their spontaneous expulsion from the crystalline domains during the self‐assembly. The best compromise between field‐effect mobility ( μ ) and switching capabilities is observed in blends containing P3HT with M w = 50 kDa, exhibiting μ as high as 1 × 10 −3 cm 2 V −1 s −1 combined with a >50% photoswitching ratio. Higher or lower M w than 50 kDa are found to be detrimental for field‐effect mobility and to lead to reduced device current switchability. The microstructure of the regioregular P3HT blend is found to be sensitive to the thermal annealing temperature, with an increase in μ and a decrease in current modulation being observed as a response to the light‐stimulus likely due to an increased P3HT‐DAE segregation, partially hindering DAE photoisomerization. The findings demonstrate the paramount importance of fine tuning the structure and morphology of bicomponent films for leveraging the multifunctional nature of optoelectronic devices. Abstract : The optimization of the light responsive nature of optically switchable organic thin‐film transistors comprising a blend of photochromic diarylethenes and poly(3‐hexylthiophene) is achieved by tuning the molecular weight and regioregularity of the conjugated polymer as well as the temperature of thermal annealing of the thin films.